Correction to: Fe-S cluster assembly in the supergroup Excavata - Peña-Diaz, Priscila; Lukeš, Julius (Journal of biological inorganic chemistry, 2018)
The article "Fe-S cluster assembly in the supergroup Excavata", written by Priscila Peña‑Diaz, Julius Lukeš was originally published electronically on the publisher's internet portal (currently SpringerLink) without open access.